Enforcement Mechanism for Market Regulation under Anti-Monopoly Laws in Pakistan and China - Aziz, Zeeshan; khalid , Maryam; Kanwal, Shamsa; Fiaz, Ali; Matiullah, Hassan; Mehmood, Yaris (International Journal of Scientific Research and Management (IJSRM), 2025)
This paper discusses the enforcement mechanisms of anti-monopoly laws in Pakistan and China, focusing on their enforcement, existing challenges, and institutional frameworks. The study begins by providing an overview of the anti-monopoly laws in the two concerned countries, highlighted by Pakistan’s Competition Act, 2010, and China’s Anti-Monopoly Law (AML) 2022. It then explores the roles of the respective regulatory bodies, comparing the powers, responsibilities, and enforcement actions of the Competition Commission of Pakistan (CCP) and the State Administration for Market Regulation (SAMR). The analysis centres on significant enforcement mechanisms, investigations into anti-competitive practices, penalties, and merger control, while also addressing the challenges faced by each country in implementing these laws, such as political intervention, institutional constraints, and sector-specific issues. Through a comparative analysis, the essay assesses the strengths and weaknesses of the enforcement frameworks in both nations, advocating for necessary changes to enhance future anti-monopoly regulation. The findings are summarized in the conclusion, offering suggestions for further market regulation under Pakistan’s anti-monopoly laws and China’s Competition Law.